ADVICE ON EFFICIENCY USING THE TOTAL RESOURCE POTENTIAL AT AGRICULTURAL ENTERPRISES - Tetyana Kalna-Dubinyuk (European Cooperation, 2016)
In the article describes advice on efficiency using the total resource potential at farms, the definition of "resource potential of agricultural enterprises" and justified his constituents and efficiency, methodical approaches to the valuation of its key elements. This definition of total resource potential by bringing all groups of agricultural production resources to the comparative form that displays one indicator. According to the methodological approaches for the establishment of resource potential in agriculture defines monetary valuation of all production resources and their overall value in certain agricultural formation. It is shown that one of the important features of the advising is to provide rapid and reliable information, as one of the important components of effective management of resource support domestic agricultural units is information provision. It is shown that the developed advisory system creates the right conditions for the development of information management, the introduction of new information and technology consulting - developing an electronic extension system with interactive consulting system during the study were used the following methods: dialectical - knowledge of the nature and features of formation of resource potential of agrarian formations; bibliographic - the study of scientific papers devoted to this issue; -evaluation system summarizing the current state of resource potential; comparison and graphics - the study of current trends in the resource potential of agricultural enterprises. It is concluded that the effective formation of the resource potential of the domestic agricultural formations advisable while increasing cost indicators improve its quality composition. Also reasonable position to ensure effective advisory process by creating and using resource potential and noted that it needs to provide scientifically grounded recommendations that would take into account all the factors engaged influenced him, and determine the effectiveness of the potential of using the electronic extension system e-Dorada.